Wahhabism, Identity, and Secular Ritual: Graduation at an Indonesian High School - Inayah Rohmaniyah; Mark Woodward (Al-Jami'ah Research Centre, 2012)
This paper concerns the social and ritual construction of social identities at Pondok Pesantren Madrasah Wathoniyah Islamiyah (PPMWI), a theologically Wahhabi oriented pesantren (traditional Islamic school) in Central Java, Indonesia. We focus on the inter-play of religious and secular symbols in the school’s graduation ceremonies (wisuda) for secondary school students and the ways it contributes to the construction of individual and social identities. Our analysis builds on Turner’s studies of the processual logic of rites of passage, Moore and Meyerhoff’s distinction between religious and secular ritual and Tambiah’s application of the Piercian concept of indexical symbols to the analysis of ritual. Theoretically we will be concerned with ritual, cognitive and social processes involved in the construction of religious identities. Empirically, we critique the common assumption that Salafi, and more specifically, Wahhabi, religious teachings contribute to the construction of exclusivist identities, social conflict and violence. In the case we are concerned with, religious tolerance and non-violence are among the defining features of Wahhabi identity.[Tulisan membahas konstruksi identitas ritual dan sosial pada sebuah pesantren yang berorientasi teologi Wahhabi, yaitu Pondok Pesantren Madrasah Wathoniyah Islamiyah (PPMWI). Diskusi akan difokuskan pada saling silang simbol-simbol agama dan sekuler dalam peringatan wisuda siswa menengah pertama serta signifikansinya dalam konstruksi identitas sosial dan individual. Analisis tulisan ini berdasarkan studi Turner mengenai logika proses dalam daur ritus (the processual logic of rites of passage), pembagian ritual agama dan sekuler oleh Moore dan Meyerhoff serta konsep Piercian mengenai indek simbolis dalam ritual oleh Tambiah. Secara teoritis, artikel ini akan mendiskusikan ritual, kognisi, dan proses sosial yang menjadi bagian dalam konstruksi identitas agama. Selain itu, penulis juga melakukan kritik terhadap pandangan umum mengenai Wahhabi yang dituduh sebagai identitas ekslusif, biang-kerok konflik sosial dan kekerasan. Penulis menemukan sebaliknya, bahwa toleransi antar agama dan anti-kekerasan adalah salah satu ciri identitas Wahhabi.]